Poeta i dźwięki w nowym mieszkaniu. Uwagi o cyklach wierszy "Trynkowanie mrówkowca" i "Niedzielojda" z tomu "Odczepić się" Mirona Białoszewskiego - Wiśniewski, Jerzy (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
A new flat in a high-rise block in Saska Kępa-Chamowo described by Miron Białoszewski in a collection of poems Odczepić się (published in 1978) is a strange and unfriendly area which the author must constantly get familiar with. Some of the factors which make it difficult for the poet to feel settled there are strange, annoying and disruptive sounds. Many poems testify how helpless Białoszewski was against the noises coming from outside the windows, behind the walls and ceiling. However, in the cycles Trynkowanie mrówkowca and Niedzielojda the poet shows how he tries to “civilize” or “domesticate” the noises by discovering their harmonious and elementary connections with music which symbolizes a superior order. Finally, it turns out that a hostile world of this high-rise block can be arranged and organized by drawing parallels between the noise and classical music. In this way it is possible to look at the acoustically irritating block of flats with a new perspective. These new acoustic relations seem to be - as other unknown situations - a new reality where one can tune in and search for the essence of being.